1961
DOI: 10.1139/z61-013
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmical Arousal From Hibernation in the Golden-Mantled Ground Squirrel, Citellus Lateralis Tescorum

Abstract: Daily observations on each of over one hundred individuals of C. lateralis by a special technique indicated that no animal remains continuously in the hibernating state longer than approximately 16 days (at an environmental temperature of 32° F). The arousals were more frequent at the beginning (i.e. in the autumn) and the ending (i.e. in the spring) of the whole hibernating period, than during the middle of this period (December and January). Adult males were found to arouse more frequently than did adult fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

1962
1962
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(75 citation statements)
references
References 3 publications
2
73
0
Order By: Relevance
“…Shavings are placed on the back of the AGS and checked every 24 h. An AGS is considered 'torpid' (hibernating) if the shavings remain on its back or considered to have been through an 'arousal' if the shavings are disturbed or missing. This 'shavings added' or 'sawdust method' is a reliable indicator of hibernation (Lyman, 1948;Pengelley and Fisher, 1961;Willis et al, 1971). Additionally, RR and responsiveness of each AGS were recorded daily for further validation of the hibernation state.…”
Section: Animals Groups and Determination Of Hibernation Statusmentioning
confidence: 99%
“…Shavings are placed on the back of the AGS and checked every 24 h. An AGS is considered 'torpid' (hibernating) if the shavings remain on its back or considered to have been through an 'arousal' if the shavings are disturbed or missing. This 'shavings added' or 'sawdust method' is a reliable indicator of hibernation (Lyman, 1948;Pengelley and Fisher, 1961;Willis et al, 1971). Additionally, RR and responsiveness of each AGS were recorded daily for further validation of the hibernation state.…”
Section: Animals Groups and Determination Of Hibernation Statusmentioning
confidence: 99%
“…The golden hamster may average three days in hibernation between arousal, while the average for the thirteen-lined ground squirrel is closer to six or seven days (Pengelley and Fisher, 1961), and bats remain torpid for more than a month. Kayser (1952) has shown that bouts of hibernation are longer during the middle of the hibernating season and this has been confirmed by Pengelley and Fisher (1961).…”
Section: Arousalmentioning
confidence: 99%
“…The cause of natural arousal is a mystery, though Strumwasser (1960) has shown that it occurs at the same time of day in the California ground squirrel which is starting the hibernating season, as if the stimulus was mediated by some sort of temperature independent biological clock. Many other hibernators demonstrate no particular diurnal pattern in arousal time, but arousals take place at fairly regular intervals (Pengelley and Fisher, 1961).…”
Section: Arousalmentioning
confidence: 99%
See 1 more Smart Citation
“…They sustain elevated T b s for Ͻ1 day, after which they return to hibernation (21,53,71). Up to 80% of a hibernating mammal's winter energy budget is consumed during these periodic arousals (9,35,66), and the consequent depletion of energy stores may contribute to overwinter mortality (71).…”
mentioning
confidence: 99%